Estimation of solute transport parameter and mass transfer coefficient in nanofiltration for solvent diluted palm oil - Lim, K. M. (2020)
Membrane technology has been gradually used as an alternative to the conventional purification method in various industries. In the advancement of membrane technology, important elements such as volumetric flux, rejections, mass transfer and interaction parameters have been frequently considered, particularly in the prediction of membrane performance. In this study, an estimation of mass transfer and solute transport parameters in organic solvent was conducted by using the Levenberg-Marquardt least squares method. Combined film theory/solution-diffusion model was selected and was correlated with experimental data to estimate the parameters. The mass transfer and solute transport parameters for the nanofiltration of acetone-diluted palm oil in SolSep 030306 membrane were successfully estimated. The correlation of mass transfer coefficient with feed concentration and stirrer speed were additionally described.